Hospitality and cosmopolitanism in the migration: Africa and the senegalese diaspora - Guijarro, Ester Massó (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The aim of this article is to defend the theoreticalpractical and epistemological entail of the philosophical notions of hospitality and cosmopolitanism, on the one hand and the relation of this conceptual binomial with the migratory fact, on the other hand. Such a refl ection will be orientated from the beginning to the Sub Saharan African region: the approach of the decolonial turn in social sciences will appear as general frame to develop an intellectual different look towards Africa and the African migration. The research methodology is the bibliographical review and the anthropological fi eldwork. Thus, to validate the theoretical argumentation with a real example, the associative experience of the Senegalese migrant community in Spain is posed, in order to show how associative autochthonous practices become experiences of hospitality and cosmopolitanism in the diaspora, and even citizenship practices, beyond a culturalist or folkloric hermeneutic.